STRATEGIC REFERENCE POINT THEORY - FIEGENBAUM, AVI; HART, STUART; SCHENDEL, DAN (Strategic Management Journal, 1996)
How can executives achieve a match between expected external environmental conditions and internal organizational capabilities that facilitates improved performance? This paper argues that a firm's choice of ‘reference points’ can help achieve strategic alignment capable of yielding improved performance and potentially even a sustainable competitive advantage. Building upon prospect theory and other relevant theoretical perspectives, the strategic reference point (SRP) matrix is developed. A firm's SRP consists of three dimensions: internal capability, external conditions, and time. A theory is developed which posits an optimal SRP structure, and propositions are offered which articulate the expected relationships between the SRP, strategic choice behavior, and firm performance. The paper closes with some suggestions for using strategic reference points in both research and practice.